PENGEMBANGAN SARANA PRASARANA RUANG RAMAH ANAK DALAM MENINGKATKAN PELAYANAN PENGUNJUNG DI KANTOR BALAI PENDIDIKAN MENENGAH KABUPATEN KULON PROGO - Waljiyah; Saryanto; Yogi Aldias Zakariyah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
High quality public service requires a balance between administrative efficiency and visitor comfort, including for members of the public who come with children. This study aims to analyze the development of child-friendly facilities in improving visitor services at the Kulon Progo Regency Secondary Education Office. The background of the study is based on the importance of public services that are not only fast and efficient but also comfortable, inclusive, and responsive to the needs of the community, including visitors who come with children. The study employed a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. Research informants consisted of office management, service staff, facility maintenance personnel, and service users. Research findings indicate that the development of facilities and infrastructure for children’s reading rooms is crucial and can improve the quality of services provided to visitors. These efforts have a positive impact on service quality, marked by increased public comfort, a more orderly service process, more manageable waiting times, and increased staff effectiveness in serving visitors’ needs. Additionally, the public has responded positively to the changes in facilities, which are now neater, more accessible, and user-friendly. It is concluded that child-friendly spaces are a simple yet effective public service innovation for sustainably improving the quality of public services.